Relationally Reflexive Practice: A Generative Approach to Theory Development in Qualitative Research. (July 2014) - Hibbert, Paul; Sillince, John; Diefenbach, Thomas; Cunliffe, Ann L.
In this article we explain how the development of new organization theory faces several mutually reinforcing problems, which collectively suppress generative debate and the creation of new and alternative theories. We argue that to overcome these problems, researchers should adopt relationally reflexive practices. This does not lead to an alternative method but instead informs how methods are applied. Specifically, we advocate a stance toward the application of qualitative methods that legitimizes insights from the situated life-with-others of the researcher. We argue that this stance can improve our abilities for generative theorizing in the field of management and organization studies.